Effects of government bailouts on mortgage modification - Agarwal, Sumit; Zhang, Yunqi (Journal of Banking & Finance, 2018)
This paper shows how liquidity infusions affect loan modification in the mortgage market. The design of pooling and servicing agreements leads mortgage servicers to prefer foreclosure over modification when they are liquidity constrained. Therefore, a positive liquidity shock is expected to boost modification rates. Using a residential mortgage dataset that includes loan-level information, we find that the Troubled Asset Relief Program significantly increased the modification rate. Our findings help us better understand the economic consequences of government intervention and have important policy implications for the renegotiation of distressed mortgages.